Dynamic model for academic school systems engineering professional - Francisco Paredes, Abimael (2017)
The research work DYNAMIC MODEL FOR ACADEMIC PROFESSIONAL SCHOOL OF SYSTEMS ENGINEERING aims to make the systemic study by outlining to understand the university system and propose dynamic models to achieve: academic efficiency, productivity and academic quality academic at the School. This research arises from the concern to improve some academic aspects and to carry out the methodology used System Dynamics; Current system analysis was performed using causal diagrams tool which allowed us to outline. For analysis of the proposed systems Causal diagrams it was also used for the proposed models and Diagrams Forrester was used. Derived results were as follows: Outlining the current dynamic performance of the academic aspects; the map of processes of academic activities; behavior by causal diagram efficient aspect; behavior by causal diagram Productivity appearance; and behavior through the causal diagram appearance Quality. To design models Efficiency, Productivity and Quality, Forrester Diagrams used. One of the main conclusions of this research is that the schemes developed by the causal diagrams shows the behavior of the systems by the elements connected where we see the loops, influences, delays, balanceamientos, and cycles which together us how much the history of the system. Models built with Forrester diagrams allow simulations of future behavior of Efficiency, Productivity, and Academic Quality.